2011
DOI: 10.1212/wnl.0b013e318211c389
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Neuro Images : Head banging without head trauma

Abstract: A 24-year-old hard rock enthusiast presented with a left-sided, intense headache. He denied head trauma, but reported "head banging" intensively during a rock concert 2 days before admission. There were no neurologic deficits. CT and MRI revealed a left-sided subdural hemorrhage (SDH) and an arachnoid cyst at the left temporal pole (figure). The patient underwent surgical evacuation of the SDH with excellent outcome. Head banging with its brisk forward and backward acceleration and deceleration likely caused t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…All 13 studies were case studies ( table 1 ). 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 The mean ± SD age was 22.8±10.5 years, with a range of 11-50 years. Sex distribution leaned heavily male (77%).…”
Section: Resultsmentioning
confidence: 99%
“…All 13 studies were case studies ( table 1 ). 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 The mean ± SD age was 22.8±10.5 years, with a range of 11-50 years. Sex distribution leaned heavily male (77%).…”
Section: Resultsmentioning
confidence: 99%
“…In six previous cases of subdural hematoma due to headbanging, two patients had an arachnoid cyst in the middle fossa, ipsilateral to the hematoma, suggesting that headbanging may cause subdural hematoma in patients with predisposing factors for subdural hematoma like an arachnoid cyst. [ 1 6 9 11 13 15 ] Although other four patients were not reported to have such predisposing factors, we think that constitutional course and little play of bridging veins (BV) in subdural space might contribute to excessive strains and rupture of itself after shifting of the brain and cerebrospinal fluid during headbanging in other patients. When the human cadaver heads were subjected to impact, the relative displacement between the brain and skull were reported to be on the order of ± 5 mm.…”
Section: Discussionmentioning
confidence: 97%
“…In medical journals, carotid dissection, subdural hemorrhage, basilar artery thrombosis, vertebral artery aneurysm, and mediastinal emphysema have been reported as severe health complications. [ 1 3 4 6 8 9 10 11 12 13 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that patients with symptomatic arachnoid cysts can safely undergo a key-hole craniotomy and drainage procedure with reported success. 6,8…”
Section: Discussionmentioning
confidence: 99%